All roads lead to Rome: Sodiation of different-stacked SnS2. (January 2020) - Ma, Zhongtao; Yao, Zhenpeng; Cheng, Yingchun; Zhang, Xuyang; Guo, Bingkun; Lyu, Yingchun; Wang, Peng; Li, Qianqian; Wang, Hongtao; Nie, Anmin; Aspuru-Guzik, Alán
Abstract: Structural symmetry variations of two-dimensional materials may significantly affect their reaction process and kinetics with alkali ions. Here, SnS2 with different structural symmetry is used as the target to be comparatively investigated the phase transition pathway and ionic diffusion upon (de)sodiation in sodium-ion batteries using in situ transmission electron microscopy and ex situ x -ray photoelectron spectroscopy in combination with first-principles calculations. Different intermediate phases, AA1 NaSnS2 for trigonal SnS2 and AB1 NaSnS2 for hexagonal SnS2, are observed after sodium ions fully occupy all O h sites. While the coming conversion/alloying reaction processes are relatively similar. The AA1/AB1 NaSnS2 sequentially transits to SnS, β-Sn and Na15 Sn4 phases starting from T d sites of SnS2 being held. Reversible reactions occur among SnS, Na15 Sn4 and Na2 Sm (2<m<8) in following cycles. Our works provide a deep understanding of the ionic diffusion and electrochemical reaction mechanisms for two-dimensional materials with different symmetry, and offer some guidance for the design of the high energy two-dimensional electrode materials. Graphical abstract: Image 1 Highlights: Successfully identify the effect of structural symmetry on the sodiation processes of SnS2 . Systematically investigate all the possible phases appeared in whole sodiation by DFT. Deeply reveal the reaction mechanism of SnS2 used as anode materials for sodium ion batteries. Anisotropic volume expansion is revealed with the largest increment along [001].